Pertanggungjawaban Pidana Mengenai Tanah yang Dikuasai Orang Lain Tanpa Hak Dalam Peraturan Perundang-Undangan - Irene Putri Kartikasari Siregar; Syafruddin Kalo; Madiasa Ablisar; Dedi Harianto (USU LAW JOURNAL, 2019)
Abstract. For Indonesia, the land has a very close relationship yam and are eternal, so that the position  of land for the Indonesian nation is a unified whole that cannot be separated from   each other. There is a banontheuse of land without permission  is entitled to attorneys,  because there are still individuals or groups who control the land without permission  are entitled to power. This led to the need to beassessed on the elements   of  the crime of possession  of land without rights. Implementation   of liability offenses charged to individuals or groups who control the land without right. This study  is  normative,  descriptive  and  analytical  explained  as well as analyzing  aphenomenon   that a criminal   offense and accountability   of the land controlled by another person without rights.There sults showed, elements of the  crime of possession  of land without the rights stipulated  in  the legislation  contained  in Article  385 of the Criminal  Code determines  the prohibition for anyone to master, sell, lease, exchange or makes debtburden (mortgaged) land that is not right as guarantee. element  "controlled  or occupied"  no element  "used" or "mortgaged"  (collateral), enough with the fulfillment  of the element controlled or occupied that it meets the criminal elements of land tenure without rights. To be governed   is also a subjective element not only individuals but must also in volveth elegal subject of a legal person or acorporation or institution under Article 385 of the Criminal Code and Article 2 inconjunction with Article 6 of the Law  51 Prpof 1960 did not set up alegal entity or acorporation as a legal subject, Though  the subject of this law is potentially  able to control the land without permission  or illegally from entitled to the land. Keywords: crime,tenure and land